ANALISA PIECES DALAM OPTIMALISASI TRAFFIC ACCESS MENGGUNAKAN SEO PADA WEBSITE PEMASARAN - Aqshal Ilham Fadhillah; Yesica Novrita Devi; Muhammad Khoirul Hasin (Proceeding Maritime Business Management Conference, 2023)
Marketing communication is a process carried out by a company in coordinating several promotional elements and other marketing activities so that communication is established with the company's consumers. Currently, there are many websites that have been widely used as promotion media of a product to find out the problems in the marketing management information system that has been implemented in the company. Therefore, it is necessary to carry out further analysis using PIECES (Performance, Information, Economic, Control, Efficiency and Service). The PIECES method is used to analyze marketing management information systems that have been implemented previously. After analyzing the existing marketing management information system, it is necessary to optimize it using the Search Engine Optimization (SEO) method to increase website visitor traffic. From the results of the analysis and application of the Search Engine Optimization (SEO) method, it was found that there were 892 visitor traffic in 1 month, 729 users obtained from Direct, 245 Referral users, 31 Organic Social users, and 17 Organic Search users. The impact of this SEO method can only be felt after 4 to 6 months ormore with the implementation of SEO methods and activities carried out continuously as long as the website still exists so that the traffic continuously increases. Based on the results obtained, sites with SEOimplementation have a much higher amount of traffic and have great potential to be used as marketing websites with a wider customer reach compared to sites that do not implement the SEO method